UPAYA PENINGKATAN PENGHASILAN PETANI SAWIT DI DESA BUKIT INDAH KECAMATAN RAKIT KULIM KABUPATEN INDRAGIRI HULU - Lisnawati, Lina; Asriwandari, Hesti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The survey was conducted in the village of Bukit Indah Sub District Rakit Kulim DistrictIndragiri Hulu. Population in this research is the oil palm agriculturist in thevillage of Bukit Indah Sub District Rakit Kulim District Indragiri Hulu. The samplingtechnique used in this survey is using purposive sampling orbased on purpose sampling, so weget a representative sample of this study were 42 respondents. Data analysis that used in thissurvey is descriptive analysis of quantitative data. Where the contents of this study contains adiscussion of the results of research is in-depth explanation and interpretation of the data thathasbeen presented. After a discussion from result given, and then it can be inferred. From thesurvey results, it can be seen that in order to fulfill the needs of live especially food needs, the oilpalm agriculturist are using adaptive strategies to survive in addressing the various issuessurrounding their life and should have avariety of efforts in order to increase the family income.The strategy to handling this problem is basically the ability of all members of the family tomanage their own assets.Keywords: Efforts, Oil Palm Agriculturist, Adaptive strategies